Les femmes sans-abri à Montréal - Cabana Renaud, Chrystiane (Université de Montréal, 1983)
Keywords: Femmes; Itinérance

Femmes, cuisines et consommation de masse au Québec, 1945-1960 - Fradet, Louise (Université Laval, 1989)
Keywords: Alimentation; Femmes

Une cité à bâtir: des femmes dans la lutte pour le changement social - Wakeling, Faye (Société, culture et religion à Montréal: XIXe-XXe siècle, 1994)
Keywords: Femmes; Église Unie

Étude longitudinale sur les modifications du réseau social et des habitudes de vie auprès de femmes socio-économiquement défavorisées - Cotte, Pierre-Marie (Université du Québec à Montréal, 1986)
Keywords: Femmes; Pauvreté

La contribution, le rôle et la place des femmes au Service de préparation au mariage de Montréal, 1944-1972 - Pelletier, Anne (Université de Montréal, 1997)
Keywords: Femmes; Mariage

Les conditions de vie des femmes: impact du règlement de location en habitation sociale - Brais, Nicole (Université Laval, 1991)
Keywords: Femmes; Locataires; Logement

La femme mariée en emploi rénuméré: une étude du travail de la femme mariée en emploi rénuméré, au point de vue de ses conséquences sur la femme elle-même, sur le bonheur conjugal ainsi que sur ses enfants d'après les données recueillies dans les enquêtes faites à Montréal en 1956 - Guilbault, Jocelyne; Lafontaine, Andrée; Lacharité, Marie-Thérèse (Université de Montréal, 1956)
Keywords: Famille; Femmes; Mariage; Travail

Une place à soi? Aspects du célibat féminin laïc à Montréal à la fin du 19e siècle - Renaud, Catherine (Université de Montréal, 1994)
Keywords: Femmes

Women and Technological Change in Nineteenth Century Montreal - Bradbury, Bettina (Women, Work and Place, 1994)
Keywords: Femmes

Le lesbianisme à Montréal entre 1950 et 1972: une analyse sociologique d'expériences vécues - Chamberland, Line (Université de Montréal, 1994)
Keywords: Femmes

The Geography of Prostitution in an Early Nineteenth-Century Urban Centre: Montreal, 1810-1842 - Poutanen, Mary Anne (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Femmes; Prostitution

Re-Working Respectability: the Feminisation of Clerical Work and the Politics of Public Virtue in Early Twentieth-Century Montreal - Boyer, Kate (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Femmes; Travail

Les procès en séparation de corps dans la région de Montréal, 1795-1879 - Cliche, Marie-Aimée (Revue d'histoire de l'Amérique française, 1995)
Keywords: Femmes; Mariage

Working Families: Age, Gender and Daily Survival in Industrializing Montreal - Bradbury, Bettina (Labour / Le travail, 1994)
Keywords: Famille; Femmes

Les séparations de corps dans le district judiciaire de Montréal, de 1900 à 1930 - Cliche, Marie-Aimée (Canadian Journal of Law and Society / La Revue Canadienne Droit et Société, 1997)
Keywords: Femmes; Mariage

"This is our Work": The Women's Division of the Canadian Department of Immigration and Colonization, 1919-1938 - Mancuso, Rebecca (Université McGill, 1999)
Anglophone women, working in a new capacity as federal civil servants, exercised a significant influence on Canadian immigration policy in the interwar years. This dissertation focuses on the women's division of the Canadian Department of Immigration and Colonization, an agency charged with recruiting British women for domestic service from 1919 to 1938. The division was a product of the women's wing of the social reform movement and prevailing theories of gender difference and anglo-superiority. Tracing its nearly twenty years of operations shows how the division, initially regarded as a source of imperial strength and a means of English Canada's cultural survival, came to symbolize the disadvantages of Canada's connection to Great Britain and supposed weaknesses inherent in the female character. This institutional study explores the real and imagined connections among gender, imperialism, and the changing socio-economic landscape of interwar Canada. Lien avec Montréal - dans la thèse
Keywords: Femmes; Fonctionnaires

To Love, Honour and Obey, Wife-Battering in Working-Class Montreal, 1869-1879 - Harvey, Kathryn (Université de Montréal, 1991)
Keywords: Famille; Femmes

Entre l'usine et la cuisine (Maison du Fier-Monde, 1984)
Keywords: Femmes; Travail

Working Families: Age, Gender, and Daily Survival in Industrializing Montreal - Bradbury, Bettina (McClelland & Stewart, 1993)
Keywords: Famille; Femmes

To Love, Honour and Obey: Wife-Battering in Working-class Montreal, 1869-1879 - Harvey, Kathryn (Urban History Review / Revue d'histoire urbaine, 1990)
Keywords: Famille; Femmes

La prostitution féminine à Montréal, 1945-1970 - Lacasse, Danielle (Université d'Ottawa, 1991)
Keywords: Femmes; Prostitution

La prostitution féminine à Montréal, 1945-1970 - Lacasse, Danielle (Boréal, 1994)
Keywords: Femmes; Prostitution

Entre le fantasme et la reconnaissance: étude pastorale de pratiques de prostitution - Nadeau, Jean-Guy (Université de Montréal, 1983)
Keywords: Femmes; Prostitution

Pigs, Cows and Boarders. Non-wage forms of Survival among Montreal Families, 1861-1881 - Bradbury, Bettina (The Challenge of Modernity: A Reader in Post-Confederation Canada, 1992)
Keywords: Famille; Femmes

Amazons and Victims: Resisting Wife-Abuse in Working-Class Montréal, 1869-1879 - Harvey, Kathryn (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1991)
Keywords: Femmes; Tempérance

Pigs, Cows, and Boarders: Non-Wage Forms of Survival among Montreal Families, 1861-91 - Bradbury, Bettina (Labour / Le travail, 1984)
Keywords: Famille; Femmes

L'Assistance maternelle de Montréal (1912-1961): un exemple de marginalisation des bénévoles dans le domaine des soins aux accouchées - Baillargeon, Denyse (Dynamis, 1999)
Keywords: Assistance maternelle; Femmes

Les politiques familiales au Québec. Une perspective historique - Baillargeon, Denyse (Lien social et Politiques, 1996)
Keywords: Enfants; Famille; Femmes

Debating Dower: Patriarchy, Capitalism and Widows' Rights in Lower Canada» - Bradbury, Bettina (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Femmes; Mariage; Veuvage

'If You Had no Money, You Had no Trouble, Did You?' Montréal Working-Class Housewives during the Great Depression - Baillargeon, Denyse (Canadian Women. A Reader, 1996)
Keywords: Crise; Famille; Femmes

If You Had no Money, You Had no Trouble, Did You?': Montreal Working-Class Housewives During the Great Depression - Baillargeon, Denyse (Women's History Review, 1992)
Keywords: Crise; Famille; Femmes

La crise ordinaire: les ménagères montréalaises durant la crise des années trente - Baillargeon, Denyse (Labour / Le travail, 1992)
Keywords: Crise; Famille; Femmes

Le renforcement des normes sur la violence maritale. Le cas de la Montreal Society for the Protection of Women and Children, 1882-1920 - Hébert, Fernand (Bulletin d'histoire politique, 1998)
Keywords: Enfants; Famille; Femmes

Ménagères au temps de la crise - Baillargeon, Denyse (Remue-ménage, 1991)
Keywords: Crise; Famille; Femmes

Travail domestique et crise économique. Les ménagères montréalaises durant la crise des années trente - Baillargeon, Denyse (Université de Montréal, 1990)
Keywords: Crise; Famille; Femmes

Ménagères au temps de la crise - Baillargeon, Denyse (Remue-ménage, 1993)
Keywords: Crise; Famille; Femmes

Surviving as a Widow in 19th - Century Montreal - Bradbury, Bettina (Urban History Review / Revue d'histoire urbaine, 1989)
Keywords: Famille; Femmes; Veuvage

Making Do: Women, Family, and Home in Montreal during the Great Depression - Baillargeon, Denyse (Wilfrid Laurier University Press, 1999)
Keywords: Crise; Famille; Femmes

Class, Culture, Family and the Law: Wife to Widow in Nineteenth-Century Quebec - Bradbury, Bettina (Programme d'études sur le Québec de l'Université McGill, 1997)
Keywords: Femmes; Mariage; Veuvage

Aspects sociaux et économiques du veuvage à Montréal au milieu du 19e siècle - Favel, Valentine (Université Lumière Lyon 2, 1991)
Keywords: Famille; Femmes; Veuvage

Absorbing Junior: the Use of Patent Medicines as abortifacients in Nineteenth Century Montreal - Gossage, Peter (The Register, 1982)
Keywords: Avortement; Femmes; Médecine

Maîtresses de maison dépareillées? L'apprentissage du travail domestique à Montréal au début du siècle - Baillargeon, Denyse (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1991)
Keywords: Enfants; Famille; Femmes

Gender at Work at Home: Family Decisions, the Labour Market, and Girls' Contributions to the Family Economy - Bradbury, Bettina (Canadian Family History. Selected Readings, 1992)
Keywords: Enfants; Famille; Femmes; Travail

The Homeless, the Whore, the Drunkard, and the Disorderly: Contours of Female Vagrancy in the Montreal Courts, 1810-1842 - Poutanen, Mary Anne (Gendered Pasts: Historical Essays in Femininity and Masculinity in Canada, 1999)
Keywords: Délinquance; Femmes; Itinérance; Prostitution

La philanthropie et la violence maritale. Le cas de la Montreal Society for the Protection of Women and Children et de la Woman's Christian Temperance Union of the Province of Quebec - Hébert, Fernand (Université du Québec à Montréal, 1999)
Keywords: Enfants; Famille; Femmes; Philanthropie

Gender at Work at Home: Family Decisions, the labour Market and Girl's Contributions to the Family Economy - Bradbury, Bettina (Canadian and Australian Labour History. Toward a Comparative Perspective, 1990)
Keywords: Enfants; Famille; Femmes; Travail

« Empêcher la famille »: Fécondité et contraception au Québec, 1920-60 - Gauvreau, Danielle; Gossage, Peter (Canadian Historical Review, 1997)
Keywords: Contraception; Famille; Femmes; Fécondité

Deviant Anonymous: Single Mothers at the Hôpital de la Miséricorde in Montreal, 1929-39 - Lévesque, Andrée (CHA / SHC, Historical Papers / Communications historiques, 1984)
Keywords: Femmes; Hôpital de la Miséricorde; Hôpitaux

L'ajustement social des anciennes de l'Institution des Sourdes-Muettes: une étude du fonctionnement social de 34 sourdes sorties à la fin ou avant la fin de leurs études de cette Institution, entre juin 1951 et juin 1960, habitant la Cité de Montréal - Girard, Jean-Charles (Université de Montréal, 1961)
Keywords: Femmes; Institution des sourdes-muettes; Sourds

Deviant Anonymous: Single Mothers at the Hôpital de la Miséricorde in Montreal, 1929-1939 - Lévesque, Andrée (Delivering Motherhood: Maternal Ideologies and Practices in the 19th and 20th Centuries, 1990)
Keywords: Femmes; Hôpital de la Miséricorde; Hôpitaux

Fréquenter les Gouttes de lait: l'expérience des mères montréalaises, 1910-1965 - Baillargeon, Denyse (Revue d'histoire de l'Amérique française, 1996)
Keywords: Enfants; Femmes; Goutte de lait; Mortalité

Care of Mothers and Infants in Montreal Between the Wars: the Visiting Nurses of the Metropolitan Life Milk Deposits and Assistance maternelle - Baillargeon, Denyse (Caring and Curing. Historical Perspectives on Women and healing in Canada, 1994)
Keywords: Assistance maternelle; Enfants; Femmes; Goutte de lait; Infirmières

The Working-Class Family Economy: Montreal, 1861-1881 - Bradbury, Bettina (Université Concordia, 1984)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (Cities and Urbanization. Canadian Historical Perspectives, 1990)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (Interpreting Canada's Past. Vol. 2. After Confederation, 1986)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (The Social Development of Canada - Readings, 1983)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (CHA / SHC, Historical Papers / Communications historiques, 1979)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

The Family Economy and Work in an Industrializing City, Montreal in the 1870's - Bradbury, Bettina (Interpreting Canada's Past. Vol. 2: Post-Confederation, 1993)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail